Pengaruh Gaya Kepemimpinan Terhadap Produktivitas Kerja Karyawan Dinas KOPERINDAG Kabupaten Tasikmalaya - Gumilar, Vera Cahya; Bayu; Sofyan, Verra Rosyalia Widia (EKOBIMA, 2025)
The problem in this research is Leadership Style with the aim of finding out the leadership style used by the agency, the productivity achieved by employees the magnitude of the influence.The research method used is a descriptive method of analysis with data collection techniques used: observation, interviews, distribution of questionnaires, literature studies and documentation studies. The population taken was 55 people. Sampling uses a saturated sample or better known as a census because it looks at the total population that can be reached by the author. From the results of data analysis, a simple linear regression equation was obtained Ŷ=39.34 + 0.57X, meaning that the Leadership Style applied by the Tasikmalaya Regency KOPERINDAG Service has a direct relationship with employee work productivity. Where if the leadership style increases once, employee work productivity will increase by 0.57 times. From the results of the correlation test, it was obtained that the value r = 0.50, which means that the leadership style used by the KOPERINDAG Service has a moderate relationship to the work productivity of the employees of the Tasikmalaya Regency KOPERINDAG Service. The results of the determination and non-determination tests show that the influence of leadership style on employee work productivity is 25%, while the remaining 75% is due to other factors. To test the hypothesis proposed, the author uses the t test by comparing the t count with t table.